MODELS OF TEACHER LEARNING - Tovboyeva Mokhinur Bozorboy kizi, (ZAMONAVIY TA'LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2024)
The article covers important information about models of teacher learning in modern education system. On the other hand, significant points about models of teaching and learning were discussed.